1997
DOI: 10.1210/jcem.82.11.4369
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Follicle-Stimulating Hormone for Normogonadotropic Clomiphene-Resistant Anovulatory Infertility: Prospective, Randomized Comparison between Low Dose Step-Up and Step-Down Dose Regimens1

Abstract: A low dose step-up and step-down regimen for induction of ovulation using urinary FSH was compared in a prospective randomized fashion in 37 normogonadotropic clomiphene-resistant oligo- or amenorrheic infertile women. The objectives was to assess potential differences in duration of treatment, ovarian stimulation (serum FSH levels), and response [serum estradiol (E2) levels and number and size of follicles]. Monitoring (blood sampling and transvaginal sonography) took place on the day of initiation of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 29 publications
3
3
0
Order By: Relevance
“…The higher multifollicular developments in the stepdown group causing a 25% of cancellations are consistent with some reports from studies on PCOS patients (Andoh et al, 1998), differing from others (van Santbrink & Fauser, 1997;Andoh et al, 1998;Balasch et al, 2001). Van Santbrink & Fauser (1997) observed a higher monofollicular development in PCOS clomiphene-resistant patients following the step-down protocol compared with the ones following the step-up (88% vs. 56%; p=0.04).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The higher multifollicular developments in the stepdown group causing a 25% of cancellations are consistent with some reports from studies on PCOS patients (Andoh et al, 1998), differing from others (van Santbrink & Fauser, 1997;Andoh et al, 1998;Balasch et al, 2001). Van Santbrink & Fauser (1997) observed a higher monofollicular development in PCOS clomiphene-resistant patients following the step-down protocol compared with the ones following the step-up (88% vs. 56%; p=0.04).…”
Section: Discussionsupporting
confidence: 90%
“…The higher multifollicular developments in the stepdown group causing a 25% of cancellations are consistent with some reports from studies on PCOS patients (Andoh et al, 1998), differing from others (van Santbrink & Fauser, 1997;Andoh et al, 1998;Balasch et al, 2001). Van Santbrink & Fauser (1997) observed a higher monofollicular development in PCOS clomiphene-resistant patients following the step-down protocol compared with the ones following the step-up (88% vs. 56%; p=0.04). This could be attributed to their basal anovulatory condition, better responding to higher initial doses followed by a more physiological decrease of rFSH than to a stepping up approach possibly leading them to a higher number of cancellations (Koundouros, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Initial experience with the step-down protocol in a series of 82 women suggested that the duration of treatment and total gonadotropin dosage were reduced compared with the low-dose step-up protocol and that monofollicular growth was more frequently achieved [50]. These findings have recently been confirmed by a prospective randomized comparison of low-dose step-up and step-down regimens in 37 clomiphene-resistant women [51]. In comparison to the step-up regimen, women treated with step-down regimen were shown to have pre-ovulatory estradiol in the normal range in 71% as opposed to 33%.…”
Section: Normal Follicular Development and The Normal Menstrual Cyclementioning
confidence: 99%